2010
DOI: 10.1038/nature09171
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myeloid leukaemia by the cell-fate determinant Musashi

Abstract: Chronic myelogenous leukemia (CML) can progress from an indolent chronic phase to an aggressive blast crisis phase1 but the molecular basis of this transition remains poorly understood. Here we have used mouse models of CML2,3 to show that disease progression is regulated by the Musashi-Numb signaling axis4,5. Specifically, we find that chronic phase is marked by high and blast crisis phase by low levels of Numb expression, and that ectopic expression of Numb promotes differentiation and impairs advanced phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
421
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 320 publications
(451 citation statements)
references
References 35 publications
22
421
3
1
Order By: Relevance
“…Genetic loss of Msi2 results in increased Numb levels and, as a consequence, functionally impairs the development and propagation of BC-CML in vivo. Interestingly, Msi2 is not only highly upregulated during human CML progression, but is also a marker for poorer prognosis in human BC-CML and de novo AMLs [57,58]. Collectively, these studies define the essential role of the RNA binding factor Msi2 as a molecular driver of cancer progression by regulating the balance between stem cell self-renewal and differentiation.…”
Section: Let-7mentioning
confidence: 86%
See 1 more Smart Citation
“…Genetic loss of Msi2 results in increased Numb levels and, as a consequence, functionally impairs the development and propagation of BC-CML in vivo. Interestingly, Msi2 is not only highly upregulated during human CML progression, but is also a marker for poorer prognosis in human BC-CML and de novo AMLs [57,58]. Collectively, these studies define the essential role of the RNA binding factor Msi2 as a molecular driver of cancer progression by regulating the balance between stem cell self-renewal and differentiation.…”
Section: Let-7mentioning
confidence: 86%
“…Msi1 inactivation alone results in barely appreciable defects during embryonic neural development, which may be due to functional redundancies among the two paralogs [56]. The second gene, Msi2, is predominantly expressed in the most immature HSC compartment within the hematopoietic organ, and during CML disease progression, Msi2 expression levels are significantly elevated in the blast crisis phase [57]. Importantly, NUP98-HOXA9 can trigger Msi2 expression, which in turn represses Numb expression.…”
Section: Let-7mentioning
confidence: 99%
“…Based on the evidence that tissue stem cells exist in many adult tissues, including the hematopoietic system, intestine, mammary gland, testis, skeletal muscle, skin, hair follicle and myocardium, other than the CNS and neural crest-derived tissue, Msi/Numb/Notch signaling is considered to be associated with many adult malignancies [2]. In fact, not only at the normal developmental stages, the Msi-signaling pathway is also reported to work during tumorigenesis in several adult tissues, including glioblastoma and esophageal, colon, pulmonary, mammary and bladder carcinomas [2,[10][11][12][13]. Intriguingly, in the case of esophageal adenocarcinoma, Msi1 expression was the highest in glands during early cancer development.…”
mentioning
confidence: 99%
“…Although a previous report showed that Msi2 gene was rearranged to form a Msi2/HoxA9 fusion gene in a chronic myeloid leukemia (CML) case with the 7p15 breakpoint [14], the recent papers reported by Ito et al [12] and Kharas et al [13] were the first reports to show clearly the relationship between Msi2-inducing pathway and hematopoietic malignancy. These two reports suggested a new strategy for the therapy of aggressive leukemia.…”
mentioning
confidence: 99%
“…So, apart from its role in neural stem cells and neuronal development, MSI2 may be involved in the maintenance of proper functioning of PV-containing GABAergic interneurons by controlling the local translation or stability of mRNAs that encode essential neurotransmitters, receptors, and channels. MSI2 is also expressed in the stem-cell compartments of other tissues and in aggressive tumors as well as playing a broad role in stemness and the determination of cell fate [35][36][37][38][39]. The detailed action of MSI2 on physiological and pathological processes requires further research.…”
Section: Combined Sample Analysismentioning
confidence: 99%